2013
DOI: 10.1017/s1041610213001245
|View full text |Cite
|
Sign up to set email alerts
|

Montreal Cognitive Assessment and Mini-Mental State Examination performance in patients with mild-to-moderate dementia with Lewy bodies, Alzheimer's disease, and normal participants in Taiwan

Abstract: The MoCA is a more sensitive instrument than the MMSE to screen AD or DLB patients from non-dementia cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…However, analyses including only those without treatment showed similar findings as the overall analysis, indicating that treatment status is not a major confounder. MMSE was used as the measure of cognition, which is less sensitive to the early cognitive changes in PD and perhaps also DLB, than other scales such as the Montreal Cognitive Assessment (MoCA) . However, our recent analysis suggests that MMSE and MoCA are equally sensitive to the cognitive change in DLB, as has been shown also in PD .…”
Section: Discussionmentioning
confidence: 98%
“…However, analyses including only those without treatment showed similar findings as the overall analysis, indicating that treatment status is not a major confounder. MMSE was used as the measure of cognition, which is less sensitive to the early cognitive changes in PD and perhaps also DLB, than other scales such as the Montreal Cognitive Assessment (MoCA) . However, our recent analysis suggests that MMSE and MoCA are equally sensitive to the cognitive change in DLB, as has been shown also in PD .…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, executive subtests—most notably verbal fluency, but also trail‐making and clock drawing—can be discouraging to patients with severe cognitive deficits, hence clinicians instinctively chose easier tests like the MMSE in this population. Nonetheless, multiple studies have shown that the MoCA in fact does not have a significant floor effect even in moderate to advanced stages of dementia …”
Section: Discussionmentioning
confidence: 99%
“…16,17 . However, the sensitivity to change in DLB has been reported to be similar in MoCA and MMSE 18 .…”
Section: Cognitive Declinementioning
confidence: 99%